Tools for Comprehensive Assessment of Fluid-Mediated and Solid-State Alteration of Carbonates Used to Reconstruct Ancient Elevation and Environments - Ingalls, Miquela; Snell, Kathryn E. (Frontiers in Earth Science, 2021)
Carbonates are ubiquitous in the rock record and provide a broad array of stable isotope-based paleoclimate proxies (i.e., δ18O, δ13C, ∆47, ∆17O, ∆48) that provide information on stratigraphy, carbon cycling, temperature, hydrology, and, the altitude of ancient land surfaces. Thus, carbonates are an essential archive for understanding the environmental and topographic history of continental terranes. However, carbonate minerals are highly susceptible to post-depositional alteration of primary isotopic values via fluid-mediated and solid-state reactions. We propose a hierarchical suite of techniques to comprehensively assess alteration in carbonates, from essential and readily accessible tools and to novel, high- resolution techniques. This framework provides a means of identifying preserved textures in differentially altered samples that contain high-value environmental information. To illustrate this progressive approach, we present a case study of Tethyan nearshore carbonates from the Paleocene Tso Jianding Group (Tibet) that were originally intended to provide a revised sea level δD value from transported organics for Tibetan paleoaltimetry studies. We demonstrate the utility of each technique in identifying chemical and crystallographic indicators of post-depositional alteration at progressively finer spatial scales. For example, secondary ionization mass spectrometry (SIMS) oxygen isotope maps of micrite and bioclasts reveals that textures that were labelled “primary” by optical inspection can yield significant isotopic heterogeneity due to grain-scale water-rock exchange. Optical and cathodoluminescence microscopy should be a required assessment of carbonate samples used in stable isotope analyses, but SIMS, PIC mapping, and other yet untapped technologies may allow distinction of primary and altered fabrics at a scale previously inaccessible.